PENGARUH PENGGUNAAN CHATGPT TERHADAP MINAT BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Septi Anggraini; Caska Caska; Filma Alia Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning interest in this study refers to students who have an inner desire to be interested in learning activities, which can be seen through student activities during lectures, whether in the form of feelings of joy, concentration, enthusiasm, and others. The use of ChatGPT is utilizing learning facilities in the form of artificial intelligence to increase student learning interest. Therefore, the purpose of this study is to determine the effect of ChatGPT use on the learning interest of students in the Economics Education study program at the University of Riau. The background of this study is the increasing use of ChatGPT in the campus environment and the low interest in learning of students. This type of research is descriptive with a quantitative approach. The subjects of the study were 109 active undergraduate students in the Economics Education Study Program, class of 2023. The sampling technique used was proportional random sampling and the Solvin formula obtained 52 respondents. The sample selection process was carried out randomly using a lottery method. Data collection was carried out by distributing questionnaires, then analyzed using descriptive analysis, analysis prerequisite tests, simple linear regression, and hypothesis testing. From the analysis carried out, there is an effect of ChatGPT use on the learning interest of students in the Economics Education Study Program at the University of Riau. With a regression coefficient of 0.345, a significance level of 0.004 (<0.05), and a calculated t-value of 2.979 > t-table of 2.009, this indicates that the more frequently ChatGPT is used, the higher the student's learning interest. The coefficient of determination (R2) of 0.151 indicates 15.1%. Meanwhile, the remaining 84.9% is influenced by other factors not included in this model. Other variables that potentially influence learning interest include Perplexcity, Gemini, Notion AI, and others.